»Fremde, ferne Welt« Mazedonienimaginationen in der deutschsprachigen Literatur seit dem 19. Jahrhundert - Langer , Benjamin (Lettre, 2019)
At present, Macedonia is again increasingly present in the German-speaking media discourse, in particular due to the so-called "name dispute" with Greece. But what is it when we talk about Macedonia? The media representation of the region often remains diffuse and is strongly influenced by stereotypes. In his comprehensive analysis, Benjamin Langer shows for the first time how this south-eastern European region was shaped in German-language texts from a terra incognita on the periphery of Europe and provided with attributions. In ten thematic chapters, he shows how powerful these images are despite their contradictions and changing instrumentalization to this day.